Building Community Resilience through Adaptive Governance: A Socio-Ecological Approach to Environmental Change - Mahturai Rian Fitra; Wiwiet Wulandari (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study aims to examine the role of adaptive governance in building community resilience to environmental change in South Sulawesi, Indonesia, by using a socio-ecological approach. It focuses on how governance structures, local knowledge, and multi-stakeholder collaboration can enhance community resilience in response to deforestation, climate change, and resource overexploitation. Subjects and Methods: The research adopted a mixed-methods approach, combining qualitative data from semi-structured interviews and focus group discussions (FGDs) with quantitative survey data. A total of 30 key informants from local communities, government, and NGOs were interviewed, and a survey was conducted among 200 households across different regions in South Sulawesi. The qualitative data were analyzed using thematic analysis, while the quantitative data were analyzed through descriptive statistics. Results: The findings highlight that adaptive governance frameworks, which emphasize local knowledge, stakeholder collaboration, and multi-level participation, are crucial for fostering resilience. However, the study also identified significant barriers to effective implementation, including political fragmentation, limited institutional capacity, and resistance to change in some communities. Despite these challenges, community-led initiatives, such as coastal management and ecosystem restoration, were found to enhance local resilience and demonstrate the potential of adaptive governance. Conclusions: This research underscores the importance of adaptive governance in addressing environmental challenges in socio-ecologically complex regions like South Sulawesi. The study emphasizes the need for inclusive, flexible, and locally relevant governance strategies. Future research should focus on expanding adaptive governance models and exploring the sustainability of community-driven adaptation efforts.